Development of Stamping Machine Module to Improve Practical Competency - Pippie Arbiyanti (Universitas Sanata Dharma, 2019)
The aim of this research is to design and manufacture a stamping machine module controlled by PLC. Stamping machine is an apllication of electro-pneumatic system in industry to print image/text on the workpieces. The result of this research is a stamping module controlled by PLC, with reliable and easy to disassemble for learning Electropneumatic Practice.